Maternal Complications in Grand Multiparous Women - Neelam, .; Shaikh, Shahida; Suleman, Aisha (Biological and Clinical Sciences Research Journal, 2025)
Grand multiparity, defined as five or more previous viable deliveries, is associated with increased maternal health risks, particularly in low-resource settings. Objective: To assess the prevalence and types of maternal complications occurring during the antepartum, intrapartum, and postpartum periods among grand multiparous women. Methods: This hospital-based descriptive observational study was conducted at Shaikh Zayed Hospital Larkana from June 2024 to December 2024. A total of 178 grand multiparous women were included in the study. Grand multiparity was defined operationally as having five or more previous viable deliveries beyond 20 weeks of gestation. Participants were admitted to the hospital either in active labor or for routine antenatal monitoring and eventual delivery. Women aged> 18 years, had delivered five or more previous viable pregnancies, and were carrying a singleton pregnancy during the current admission were included in the study. Results: The mean age of participants was 34.6 years. Anemia (23.6%) and hypertensive disorders (10.1%) were the most common antepartum complications. Intrapartum issues included prolonged labor (9.6%) and malpresentation (6.7%), with 34.3% requiring cesarean section. Postpartum complications were present in 27.0% of cases, most commonly postpartum hemorrhage (14.6%) and retained placenta (6.2%). Overall, 56.7% of women experienced at least one complication. Despite this, no maternal deaths occurred during the study period. Conclusion: It is concluded that grand multiparity significantly increases the risk of maternal complications. Targeted antenatal care, timely obstetric intervention, and effective postpartum management are crucial to improving outcomes in this high-risk group.